Relative Prices, Economic Growth and Tax Policy - Sarel, Michael (IMF Working Papers; Working Paper, 1995)
This paper examines the role of relative prices in economic growth and the possibility that relative prices are (or can be) partly determined by tax policy. In the opening section, the paper links relative prices to tax policy. Using an extension to a standard model of economic growth, it demonstrates that under certain conditions a simple tax policy, that determines the relative price of investment, can affect the investment rate and the permanent growth rate of the economy. The paper develops a method to obtain consistent data on relative prices for a large set of countries. Using these data in cross-country regressions, it examines how economic growth is affected by relative prices. The results of these empirical tests identify the relative prices as a key factor affecting investment and growth.